2005
DOI: 10.1529/biophysj.105.061192
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Spectra of Photoactive Yellow Protein Chromophores in Vacuum

Abstract: The absorption spectra of two photoactive yellow protein model chromophores have been measured in vacuum using an electrostatic ion storage ring. The absorption spectrum of the isolated chromophore is an important reference for deducing the influence of the protein environment on the electronic energy levels of the chromophore and separating the intrinsic properties of the chromophore from properties induced by the protein environment. In vacuum the deprotonated trans-thiophenyl-p-coumarate model chromophore h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
137
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(157 citation statements)
references
References 45 publications
18
137
2
Order By: Relevance
“…As pointed out earlier, double-bond twisting must include the effect of nuclear couplings to other bonds and electronic͞resonance effects. In a very recent report (30), the gas-phase absorption spectrum of the PYP chromophore indicates that the excitation energy is lower than calculated value (22), indicating that an excess vibrational energy is sufficient for double-bond twisting. Moreover, recent molecular dynamics calculations for the protein and in vacuo support the involvement of the double-bond twisting (31).…”
Section: Resultsmentioning
confidence: 85%
“…As pointed out earlier, double-bond twisting must include the effect of nuclear couplings to other bonds and electronic͞resonance effects. In a very recent report (30), the gas-phase absorption spectrum of the PYP chromophore indicates that the excitation energy is lower than calculated value (22), indicating that an excess vibrational energy is sufficient for double-bond twisting. Moreover, recent molecular dynamics calculations for the protein and in vacuo support the involvement of the double-bond twisting (31).…”
Section: Resultsmentioning
confidence: 85%
“…[14] The gas-phase absorption spectra were recorded at the electrostatic ion storage ring ELISA, [15] which has previously been used to study photoabsorption of biological chromophores (see, for example, reference [16]), and in particular those of the PYP. [9,10,17] Briefly, deprotonated ions of the three PYP chromophore derivatives (shown in Scheme 1) were produced in the gas phase by using electrospray ionization. After pretrapping for up to 100 ms in a multipole ion trap with room temperature and having He as the buffer gas, a bunch of ions were accelerated to 22 keV, magnetically mass selected, and injected into ELISA.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…[1] In the case of PYP, the absorption of pCA À in aqueous phase is strongly blueshifted with respect to the gas-phase spectrum: it presents a maximum of absorption at 4.35 eV (285 nm) and a shoulder at 3.97 eV (312 nm). [9] The absence of perturbations from a surrounding medium makes gas-phase absorption spectra a better reference than those obtained in solution for evaluating protein tuning and, importantly, for tests of ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[35] Steady-state absorption spectra of anionic p-coumaric acid and a thioester analogue have been recently measured in vacuo. [39] A time-resolved study of another isolated analogue was recently reported, showing that the initial twisting motion occurs on the same timescale in the gas-phase as inside the protein, though subsequent channeling through the conical intersection is less efficient, owing to the need for excess energy redistribution by intramolecular vibrational relaxation (IVR). [40] p-Coumaric acid is present in its anionic form in PYP.…”
Section: Introductionmentioning
confidence: 99%